2020
DOI: 10.3390/agronomy10121893
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Cowpea (Vigna unguiculata (L.) Walp.) Landraces Suggests Central Mozambique as an Important Hotspot of Variation

Abstract: Cowpea is a multiple-purpose drought-tolerant leguminous pulse crop grown in several dry tropical areas. Its domestication center is thought to be East or West Africa, where a high level of genetic diversity is apparently still found. However, detailed genetic information is lacking in many African countries, limiting the success of breeding programs. In this work, we assessed the genetic variation and gene flow in 59 Vigna unguiculata (cowpea) accessions from 10 landraces spanning across six agro-ecological z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…However, according to our results, Mozambican cowpea landraces retain a high level of morphological diversity, corroborating a previous genetic analysis that showed a high degree of genetic admixture [17]. The two cultivars also showed no clear differentiation with the wild accessions collected in the landraces suggesting that the genetic diversity of these two commercial varieties were still close to that of the wild accessions.…”
Section: Diversity In Landraces and Cowpea Commercial Varietiessupporting
confidence: 90%
See 4 more Smart Citations
“…However, according to our results, Mozambican cowpea landraces retain a high level of morphological diversity, corroborating a previous genetic analysis that showed a high degree of genetic admixture [17]. The two cultivars also showed no clear differentiation with the wild accessions collected in the landraces suggesting that the genetic diversity of these two commercial varieties were still close to that of the wild accessions.…”
Section: Diversity In Landraces and Cowpea Commercial Varietiessupporting
confidence: 90%
“…However, it can be misleading if used alone, mainly to track intra-landrace variation [32]. For instance, a previous genetic study on cowpea landraces found no specific genetic clustering in the different AEZs [17], in accordance also with the morphological results found here. However, that study, although based on a small sample size, revealed the existence of four different genetic groups that we did not find here: one cluster was predominant and grouped all accessions from North Zambezia and most accessions from Sofala and Central Manica; the second cluster characterized Central and South Zambezia accessions; the third clustered accessions from North Manica as well as Central Sofala; the fourth cluster was exclusively composed of accessions from South Manica.…”
Section: Importance Of Morphological Traits In Cowpea Landracessupporting
confidence: 88%
See 3 more Smart Citations